Business Ethics (Open textbook library., 2018)
Business Ethics is designed to meet the scope and sequence requirements of the single-semester business ethics course. This title includes innovative features designed to enhance student learning, including case studies, application scenarios, and links to video interviews with executives, all of which help instill in students a sense of ethical awareness and responsibility.